Building a foundation for gene family analysis in Rosaceae genomes with a novel workflow: A case study in Pyrus architecture genes - Zhang, Huiting; Wafula, Eric K.; Eilers, Jon; Harkess, Alex E.; Ralph, Paula E.; Timilsena, Prakash Raj; dePamphilis, Claude W.; Waite, Jessica M.; Honaas, Loren A. (Frontiers in Plant Science, 2022)
The rapid development of sequencing technologies has led to a deeper understanding of plant genomes. However, direct experimental evidence connecting genes to important agronomic traits is still lacking in most non-model plants. For instance, the genetic mechanisms underlying plant architecture are poorly understood in pome fruit trees, creating a major hurdle in developing new cultivars with desirable architecture, such as dwarfing rootstocks in European pear (Pyrus communis). An efficient way to identify genetic factors for important traits in non-model organisms can be to transfer knowledge across genomes. However, major obstacles exist, including complex evolutionary histories and variable quality and content of publicly available plant genomes. As researchers aim to link genes to traits of interest, these challenges can impede the transfer of experimental evidence across plant species, namely in the curation of high-quality, high-confidence gene models in an evolutionary context. Here we present a workflow using a collection of bioinformatic tools for the curation of deeply conserved gene families of interest across plant genomes. To study gene families involved in tree architecture in European pear and other rosaceous species, we used our workflow, plus a draft genome assembly and high-quality annotation of a second P. communis cultivar, ‘d’Anjou.’ Our comparative gene family approach revealed significant issues with the most recent ‘Bartlett’ genome - primarily thousands of missing genes due to methodological bias. After correcting assembly errors on a global scale in the ‘Bartlett’ genome, we used our workflow for targeted improvement of our genes of interest in both P. communis genomes, thus laying the groundwork for future functional studies in pear tree architecture. Further, our global gene family classification of 15 genomes across 6 genera provides a valuable and previously unavailable resource for the Rosaceae research community. With it, orthologs and other gene family members can be easily identified across any of the classified genomes. Importantly, our workflow can be easily adopted for any other plant genomes and gene families of interest.